2008
DOI: 10.1523/jneurosci.3791-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Role of the Depolarizing Chloride Gradient Revealed by Global Overexpression of KCC2 from the Onset of Development

Abstract: GABA-and glycine-induced depolarization is thought to provide important developmental signals, but the role of the underlying chloride gradient has not been examined from the onset of development. We therefore overexpressed globally the potassium-chloride cotransporter 2 (KCC2) in newly fertilized zebrafish embryos to reverse the chloride gradient. This rendered glycine hyperpolarizing in all neurons, tested at the time that motor behaviors (but not native KCC2) first appear. KCC2 overexpression resulted in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
98
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 48 publications
(75 reference statements)
11
98
0
Order By: Relevance
“…With the observation that the activation of chloride-permeable GABA A receptors (GABA A -Rs) depolarizes developing neurons (Cherubini et al, 1991), it was proposed that part of the trophic action of GABA relies on membrane depolarization and subsequent activation of voltage-dependent calcium channels (BenAri et al, 2007). Consistent with this hypothesis, early conversion of GABA-induced depolarization into hyperpolarization impaired synapse formation and dendritic development of the target neurons both in vitro (Chudotvorova et al, 2005) and in vivo (Ge et al, 2006;Cancedda et al, 2007;Wang and Kriegstein, 2008;Reynolds et al, 2008).…”
Section: Introductionsupporting
confidence: 53%
“…With the observation that the activation of chloride-permeable GABA A receptors (GABA A -Rs) depolarizes developing neurons (Cherubini et al, 1991), it was proposed that part of the trophic action of GABA relies on membrane depolarization and subsequent activation of voltage-dependent calcium channels (BenAri et al, 2007). Consistent with this hypothesis, early conversion of GABA-induced depolarization into hyperpolarization impaired synapse formation and dendritic development of the target neurons both in vitro (Chudotvorova et al, 2005) and in vivo (Ge et al, 2006;Cancedda et al, 2007;Wang and Kriegstein, 2008;Reynolds et al, 2008).…”
Section: Introductionsupporting
confidence: 53%
“…We have recently presented evidence that KCC2 oligomers are connected by disulfide bridges (17), whereas a recent study has observed sensitivity of KCC2 oligomers to SDS (18). We could not investigate the oligomeric status of the KCC2 mutants because we noticed strong aggregation of the proteins after heterologous expression in HEK-293 cells, 5 which is consistent with the findings of Uvarov et al (18). Therefore, future studies have to address the precise role of the cysteine residues, such as their involvement in intra-and intermolecular disulfide bonds.…”
Section: Discussionmentioning
confidence: 86%
“…In mammals, the family consists of the four members KCC1 -KCC4, which are involved in different fundamental physiological processes. KCC2 is essential for the hyperpolarizing action of inhibitory neurotransmitters (1)(2)(3)(4)(5). Accordingly, null mice die perinatally (2), and loss of the splice variant KCC2b leads to generalized seizures (6).…”
mentioning
confidence: 99%
“…However, synaptic scaling did not appear to be required to maintain the patterning of motor activity in vivo, which likely forms as a consequence of an intrinsic developmental program. It is interesting to note that complete blockade of glycinergic activity in zebrafish embryos has a drastic effect on neurogenesis, resulting in the loss of half the spinal neurons and indicating that there is a minimal activity dependence for these early steps of differentiation in development Reynolds et al, 2008). The milder disruptions in glycinergic function observed in a glycine transporter mutant indicate that glycinergic strength is also susceptible to a form of synaptic homeostasis over a period of several days (Mongeon et al, 2008).…”
Section: Behavioral Consequencesmentioning
confidence: 99%